Grain and Seed Proteins Functionality 2021
DOI: 10.5772/intechopen.96204
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-Mutants of Sorghum bicolor (L.) Moench with Improved Digestibility of Seed Storage Proteins

Abstract: Modification of the composition of grain storage proteins is an intensively developing area of plant biotechnology, which is of particular importance for sorghum – high-yielding drought tolerant crop. Compared to other cereals, the majority of sorghum cultivars and hybrids are characterized by reduced nutritional value that is caused by a low content of essential amino acids in the seed storage proteins (kafirins), and resistance of kafirins to protease digestion. RNA interference (RNAi) by suppressing synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…It is noteworthy that among the F 1 hybrids with the CMS line A2 KVV-114, one plant that was PCR positive for the nos-promoter but PCR negative for the ubi1-intron was found. We previously found a similar case among T 1 plants (Elkonin et al, 2021). These facts indicate that in some cases there may be a disturbance of the integrity of the integrated T-DNA and the elimination of the genetic construct for silencing.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…It is noteworthy that among the F 1 hybrids with the CMS line A2 KVV-114, one plant that was PCR positive for the nos-promoter but PCR negative for the ubi1-intron was found. We previously found a similar case among T 1 plants (Elkonin et al, 2021). These facts indicate that in some cases there may be a disturbance of the integrity of the integrated T-DNA and the elimination of the genetic construct for silencing.…”
Section: Resultssupporting
confidence: 60%
“…1-3, 190-1, 190-2, 190-4), as well as the progeny of plant No. 190-3, which was PCR negative for the ubi1-intron, but PCR positive for the nos-promoter (Elkonin et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the earlier observations for reducing the anti-nutrients, it can be observed that RNAi and gene editing are the two major techniques that are used in tissue-specific reduction in major crops ( Figure 3 ) ( Perera et al 2018 ; Elkonin et al 2021 ). Although the initial investigations have been conducted with reduced anti-nutrients, a standard protocol for strategic reduction of anti-nutrients is crucial in crops such as pulses needs to be reinforced in future.…”
Section: Advanced Genetic Approaches For Developing Sustainable Food ...mentioning
confidence: 93%